TRANSAKSI E-COMMERCE (JUAL BELI ONLINE) DALAM PERSPEKTIF EKONOMI SYARIAH - Irfan Mujahidin; Hadi Susilo (Universitas Mathla’ul Anwar Banten, 2023)
The era of digitalization has led to changes the demands of human life which growing up to innovation and new lifestyles in the business world, through e-commerce. E-commerce is a business transaction model through the internet that can be done anytime and anywhere. The emergence of e-commerce transactions has alarmed the Islamic community, both in terms of security and shari'ah economic law. This study aims to analyze the practice of e-commerce the correlation based on the perspective of Shari’ah economic law, by using the research method used is a literature study approach. This study found important notes that e-commerce practice based on shari'ah law, can be justified because it has identicals with buying and selling Bai` As-salam if it fulfills matters into obligations in the Baii’ussalam.